Complex Terrain : Megacities and the Changing Character of Urban Operations - Valeriano, Brandon; Breitenbauch, Henrik; Jensen, Benjamin M. (Book collections on Project MUSE., 2019)
"This book explores military operations, including indirect support to other interagency actors and functions in dense urban terrain and megacities. Dense urban terrain describes urban areas with high population densities that, in the developing world, often outstrip the capacity of local governance systems to exert formal control. The term megacity describes a city with a population of 10 million or more. These environments define patterns of human settlement. In 1950, only 30 percent of the world's population lived in cities compared to more than 55 percent in 2018. Much of this growth is concentrated in large, urban centers that connect a global flow of goods and ideas. By 2030, there will be more than 40 of these megacities"--